Towards Digital Transformation: Serverless Function Deployment Strategies - Cabrera-Silva, Armando; Carrillo-Verdún, José; Martínez-Palacios, Patricio; Guamán-Coronel, Daniel-Alejandro (Revista Facultad de Ingeniería, 2021)
Digital transformation is a great asset for companies that evolve and drive their activities towards new ways where technology is a great ally, in this evolution, cloud computing plays a key role for transformation. Each company measures its performance through a business model enabled and managed in the cloud and considers the customer experience to differentiate its strategy and opt for technological solutions that make them different from the market competitors. As a strategic tool for digital transformation, moving from technological solutions from a local environment to one of serverless computing is the next step in the evolution of software. This allows software engineers to focus on coding for services, microservices, or functions to meet time-to-market without thinking too much on the complexity to implement and maintain the infrastructure. In this work, we propose a strategy to build and implement functions using a set of serverless runtimes provided by different Cloud Service Providers (CSPs). For the validation, a guided experimentation is carried out in three scenarios, considering the performance of the workload in each runtime and the average execution time of each CSP, which are monitored through analysis and visualization tools. The performance value associated with each CSP allows defining a serverless computing (FaaS) deployment strategy.